ZnSe-based organic–inorganic hybrid structure ultraviolet avalanche photodiodes with long lifetime and its device integration. (5th January 2015) - Inoue, Ryoichi; Abe, Tomoki; Fujimoto, Takeru; Ikadatsu, Noriyuki; Tanaka, Kenta; Uchida, Shigeto; Tazue, Akio; Kasada, Hirofumi; Ando, Koshi; Ichino, Kunio
Abstract: We have developed organic [poly(3, 4-ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS)]–inorganic [ZnSSe] hybrid structure ultraviolet avalanche photodiodes (UV-APDs) with a long device lifetime and integrated APD arrays. The active layer is ZnSSe grown by molecular beam epitaxy (MBE) and the window p*-type layer is PEDOT:PSS formed by the inkjet method. The device exhibits a lifetime of more than 100 d and an APD operation of more than 500 times. We integrated 3-element APD array separated only by a window spot of PEDOT:PSS. The present array device in the APD operation shows no detectable photosignal cross-talk between the neighboring APDs.